Choriocarcinoma with uterine rupture presenting as acute haemoperitoneum and shock - Gueye, Mamour; Gueye, Mame Diarra Ndiaye; Thiam, Ousmane; Toure, Youssou; Cisse, Mor; Wade, Mouhamadou; Diouf, Aliou; Mbaye, Magatte; Moreau, Jean Charles (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Choriocarcinoma is a rare neoplasm and a malignant form of gestational trophoblastic disease. Invasive mole may perforate uterus through the myometrium resulting in uterine perforation and intraperitoneal bleeding. But uterine perforation due to choriocarcinoma is rare. We present a case of a young woman who presented 1 year after uterine evacuation of a molar pregnancy with invasive choriocarcinoma complicated by a uterine rupture and haemoperitoneum.